2011
DOI: 10.1002/pbc.23025
|View full text |Cite
|
Sign up to set email alerts
|

Auditory complications in childhood cancer survivors: A report from the childhood cancer survivor study

Abstract: Background-Studies have found associations between cancer therapies and auditory complications, but data are limited on long-term outcomes and risks associated with multiple exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 42 publications
4
66
2
1
Order By: Relevance
“…Radiation therapy also increases the risk of ototoxicity, and survivors >5 years after diagnosis remain at risk for the development of ototoxicity. 12,19 We found that 6 patients had a 5-year progression of hearing loss, and 4 of them had received radiation for head lesions. Fortythree percent patients with hearing loss (ZBrock grade1) also exhibited hearing loss at low frequencies that were not defined in the Brock criteria.…”
Section: Discussionmentioning
confidence: 92%
“…Radiation therapy also increases the risk of ototoxicity, and survivors >5 years after diagnosis remain at risk for the development of ototoxicity. 12,19 We found that 6 patients had a 5-year progression of hearing loss, and 4 of them had received radiation for head lesions. Fortythree percent patients with hearing loss (ZBrock grade1) also exhibited hearing loss at low frequencies that were not defined in the Brock criteria.…”
Section: Discussionmentioning
confidence: 92%
“…Especially when young children are seriously ill, their cooperation and attention may be reduced, which can lead to hearing test results that have poor reliability, and to overall low testing rates . In all cases, though, audiological monitoring for several years after cancer treatment is important as hearing loss may only appear many years later particularly for patients treated with cranial radiation …”
Section: Discussionmentioning
confidence: 99%
“…People who have experienced major life events including post-traumatic stress disorder, serious illness of close relatives, death of family, serious problems with friends, major financial crisis, valuables stolen, being bullied, violence at home, sexual abuse or running away from home were also more likely to experience ever hearing loss problem or that in the last 12 months. [5,6] and it was observed that patients who had hearing loss primarily had bilateral symmetric sensorineural hearing loss [7]. Moreover, one recent systematic review has also indicated that patients receiving radiotherapy for head and neck tumors could be at risk of developing sensorineural hearing loss, although high-quality research is still lacking [8].…”
Section: Main Findingsmentioning
confidence: 95%